A Study of The Influence of People and Culture On The Acceptance Of The Smart Factory System In PT. XYZ Group Company Using The Technology Acceptance Model (TAM) - Nugroho, Aji; Pasaribu, Rina Djunita (International Journal of Scientific Research and Management (IJSRM), 2025)
This paper examines the people and cultural factors that may influence employee acceptance of the smart factory system at PT. XYZ Group company in order to support the achievement of INDI4.0 certification. A questionnaire was developed based on the extended technology acceptance model (TAM). A total sample of 407 employees involved both shopfloor and backoffice employees who interact directly with the smart factory system. After conducting reliability and validity checks, the hypothesized model was estimated using structural equation modeling. The findings of this study revealed that perceived ease of use (PEOU), culture (C), and facilitating conditions (FC) were significant determinants of behavioral intention (BI) and use (AU) of the smart factory system. While perceived usefulness (PU), perceived quality of work life (QWL), and computer self-efficacy (SE) did not have a significant effect..